The impact of remimazolam sedation during neuraxial anesthesia on perioperative cognitive function in elderly patients: a multicenter randomized controlled study - Qiao, Dan; Kang, Jia-Min; Zhang, Rui; Zong, Lin-Yue; Xu, Ying; Zhang, Wei-Wei; Zhou, Qi; Li, Yan; Han, Tao; Zhang, Yue-Ming; Yin, Li-Jun; Xu, Jin; et al. (Frontiers in Pharmacology, 2025)
BackgroundRemimazolam, a novel ultra-short-acting benzodiazepine, is a potential sedative for non-general anesthesia surgery in the elderly. This study aimed to investigate the appropriate sedative dosage of remimazolam and its effects on perioperative cognitive function in elderly patients undergoing non-general anesthesia surgery.MethodsThis multicenter, placebo-controlled trial enrolled 330 elderly patients undergoing non-general anesthesia procedures at eight centers in China from July 2021 to February 2022, with 238 ultimately completing the study. The primary endpoints were the dose of successful sedation with remimazolam and the changes in perioperative cognitive function. Adverse events were recorded to assess drug safety.ResultsThe induction dose of remimazolam for sedation in spinal anesthesia in elderly patients was 5.38 mg (95% confidence interval [CI], 5.20–5.56), maintained at a rate of 0.223 mg·kg−1·h−1 (95% CI, 0.201–0.237) with no serious adverse effects. Compared with the standard saline group, there was no statistical difference in the MMSE scores on Day 2 morning (P = 0.886), Day 2 afternoon (P = 0.864), and Day 7 (P = 0.613), and no statistical difference in the MoCA scores on Day 2 morning (P = 0.687), Day 2 afternoon (P = 0.827), and Day 7 (P = 0.483) in remimazolam group.ConclusionRemimazolam besylate is an effective sedative for elderly patients undergoing neuraxial anesthesia. It was successfully induced at a dose of 5.38 mg and maintained at 0.223 mg·kg−1·h−1, demonstrating a good safety profile without affecting short-term postoperative cognitive function.Clinical Trial Registrationhttp://www.chictr.org.cn (ChiCTR2100048744).